Multidimensional aspect of corporate entrepreneurship in family business and SMEs: A systematic literature review - Indra Wahyudi; Arif Imam Suroso; Bustanul Arifin; Rizal Syarief; Meika Syahbana Rusli (Economies, 2021)
This study aimed to review and analyze corporate entrepreneurship (CE) within family businesses and small and medium enterprises (SMEs), providing a review of the current state of research and suggesting a future research agenda. In a systematic literature review, 1040 articles indexed in Scopus were initially subjected to bibliometric and qualitative analysis. Finally, 53 papers published in various academic journals, focusing on corporate entrepreneurship, family businesses, and SMEs, were subjected to bibliometric analysis and qualitative research to identify the new potential state of the art in corporate entrepreneurship. CE in family businesses and SMEs is not a general research trend in the entrepreneurial area. This research shows that the literature on CE models and tools in family businesses and SMEs is still sparse. The review results correlate the actors of CE, behavior, and activities, including entrepreneurial orientation, entrepreneurial management, and entrepreneurial leadership and performance, as outcomes in family business and SMEs.
Keywords: 330; entrepreneurial orientation; bibliometric analysis; corporate entrepreneurship; family business; firm performance; small and medium enterprise; structured literature review